Intensified neoadjuvant chemoradiotherapy in locally advanced rectal cancer: impact on long-term quality of life - Kripp, Melanie; Wieneke, Julia; Kienle, Peter; Welzel, Grit; Brade, Joachim; Horisberger, Karoline; Wenz, Frederik; Post, Stefan; Gencer, Deniz; Hofmann, Wolf-Karsten; Hofheinz, Ralf-Dieter (European journal of surgical oncology, 2012)
Aims: In spite of advances in rectal cancer surgery and the use of preoperative 5-fluorouracil-(5-FU) based chemoradiotherapy (CRT) in stage II and III disease distant metastases still occur in about 35-40% of the patients. Intensified preoperative CRT (ICRT) using other drugs in conjunction with 5-FU has been investigated in order to improve the pathological complete remission (pCR) rate and thereby prognosis of patients with locally advanced rectal cancer. However, acute toxicity, especially diarrhea, was reported to be high and no improvement in pCR rates has been observed in randomized trials. Long-term results of these trials are pending. In the present analysis we investigated the impact of ICRT on health related quality of life and long term toxicity. Methods: The present study included 119 patients with locally advanced rectal cancer who underwent neoadjuvant CRT followed by surgery within controlled clinical trials. Patients received ICRT (n = 83) or standard CRT (n = 36). Evaluation of HRQoL was performed using EORTC QLQ-C30 and QLQ-CR29 questionnaires. Results: The overall rating of global health status/QLQ scale of the EORTC QLQ-C30 questionnaire was identical in both patient groups but patients in the CRT group showed better results in four out of nine function scales. Concerning symptom scales, patients in the CRT arm exhibited significantly less diarrhea (p = 0.028) and less disorders with taste (0.042). Conclusions: This data suggests that higher gastrointestinal acute toxicity caused by ICRT might lead to a higher risk of long-term deterioration of “gastrointestinal QoL”. Future results of randomized trials investigating ICRT versus CRT should be discussed in the light of long-term QoL data.
Available online 18 February 2012
Gesehen am 21.06.2018